Città come preda di René Pollesch, liberamente ispirato alle ricerche dello spaceLab - Karschnia, Alexander (Kritik. Rivista di letteratura e critica culturale, 2024)
The contribution investigates through the work Stadt als Beute the theatre of René Pollesch. Such theater is a dramatic discourse, just as the discourse of philosophy is a theater, the theatrum philosophicum, that is, as Deleuze puts it, a “series” that takes place in a “multiple, polyscenic, simultaneous theater, fragmented into scenes that ignore each other and make signs, and where without representing (copying, imitating) anything, masks dance, bodies shout, hands and fingers gesticulate”.